Конец и вновь начало - Гумилев Лев Николаевич (Сочинения Л. Н. Гумилева, 1997)
Экземпляры: СЭ (20000601) / Инвентарный номер: 1034769 / Цена: 40.00 / Сис.шифр: 63.5 / Авт.знак: Г 94 / ГРНТИ: 03 / ББК: 63.51(0)